Cover. Issue 6 (December 2014) - Unknown
<x xml:space="preserve">Abstract</x> Rhodymenia cf. rhizoides in the low intertidal of Gwaii Haanas; a species with a predominantly disjunct distribution between California and northern British Columbia. [Vol. 50, No. 6, pp. 968–974]